Analysis of genetic diversity in accessions of Irvingia gabonensis (AubryLecomte ex O Rorke) Baill - Ude, G.N.; Dimkpa, C.O.; Anegbeh, P.O.; Shaibu, A.A.; Tenkouano, A.; Pillay, M.; Tchoundjeu, Z. (2006)
Amplified fragment length polymorphism (AFLP) was used to assess genetic diversity and relationships among 15 accessions of Irvingia gabonensis collected from Cameroun, Gabon, and Nigeria. Twelve AFLP+3 primers produced 384 polymorphic fragments. Average genetic distance (AGD) between the 15 accessions was 58.7% (32-88%). AGD and range of genetic distance among accessions from Cameroun, Nigeria and Gabon were 62% (53-76%), 52% (32.3 – 84.8%) and 50% (45- 53%), respectively, indicating more genetic diversity in Cameroun than Nigeria and Gabon. The unweighted pair-group method of the arithmetic average (UPGMA) and principal coordinate analysis (PCO) showed a clear distinction between the Gabon and Nigeria accessions into two separate clusters, with accessions from Cameroun overlapping them. Principal coordinate analysis (PCO) indicated a closer relationship between accessions from Cameroun and Gabon. In general the Cameroun germplasm appears to be a bridge between the genetically isolated Nigeria and Gabon accessions. This overlap of Gabon and Nigerian accessions by the accessions from Cameroun may be an indication that Cameroun is the center of diversity of I. gabonensis and also the primary source of original materials grown in the other countries. More collection in Cameroun is necessary to ensure the optimum collection and preservation of the existing genetic diversity in I. gabonensis.